DEVELOPING PROBLEM-SOLVING SKILLS IN MANAGING DIGITAL LEARNING - Taweepong, Piyapong; Phewngam, Sawitree; Sirikanna, Jarmon; Utawan, Sombat (Journal of MCU Nakhondhat, 2023)
The Objectives of this research article were to study problems and forms of teaching and learning activities in developing students' problem-solving skills to create guidelines for developing problem-solving skills in digital learning management. The scope of this research consisted of students from Demonstration School of Suan Sunandha Rajabhat University and the research sample was Mathayomsuksa 4 students, first semester, academic year 2022 by purposive sampling. Research tools include: 1) Problem-Based Learning Plan 2) learning achievement test About moving in a straight line using a Interactive Simulations 3) problem-solving skills assessment form 4) Observation form for learning characteristics. The statistics used to analyze the data were mean ( ), standard deviation (S.D.), and t-test for dependent. The results showed that The learning achievement in rectilinear motion using interactive simulations with problem-based learning management of Mathayomsuksa 4 students after learning was statistically significantly higher than before learning. At the .05 level, in terms of problem-solving skills of the learners, it was found that After using the problem-based learning management, the learners had higher problem-solving skills than before learning at the statistical significance level of .05 and learners' interest in learning after using the learning management plan by using the problem as a basis. The overall picture after learning has a higher level.